The Effect of Giving Mangrove Leaf Extract (Rhizopora apiculata) on The Immune System of Goldfish (Cyprinus carpio) Infected with Aeromonas hydropila Bacteria - Maknun, Lu'lu'il; Azhar, Fariq; Mulyani, Laily (Jurnal Biologi Tropis, 2024)
Goldfish (Cyprinus carpio) is a type of freshwater fishery commodity whose production activities are currently growing rapidly because they are in great demand by the public. Giving Rhizopora apiculate mangrove leaf extract can reduce the number of bacteria Vibrio in vannamei shrimp so that Rhizopora apiculate mangrove leaves can be used as a natural immunostimulant. The aim of this research is to determine the effect of administering Rhizopora apiculata mangrove leaf extract at different doses on the immune system of goldfish infected with Aeromonas hydrophila bacteria. This research was carried out for 60 days at the Fish Production and Reproduction Laboratory, Aquaculture Study Program, Mataram University. The method in this study used a completely randomized design with 5 treatments and 3 repetitions. The results of the study showed that P2 was the best result that was able to improve the immune system of young mothers after the challenge test, this can be seen from the erythrocy value obtained at 5.41 x 106 cells/mm3, the leukocyte value at 6.06 x 104 cells/mm3, hemoglobin 10.7%, hematocrit 21.2%, lymphocytes 73.3%, monocytes 37.3%, neutrophils 32.3%, platelets 36.6% and phagocytic activity 34, 5%. The conclusion from the research that has been carried out is that the addition of R. apiculta mangrove leaf extract to goldfish feed has a significantly different effect on the erythrocyte, leukocyte and hematocrit levels of goldfish (C. carpio). The addition of mangrove leaf extract at a dose of 1% to goldfish is the right dose which can improve the body's defense system in goldfish.